종합병원 간호사의 직무 스트레스가 이직의도에 미치는 영향: 소진의 매개효과와 직무만족의 조절효과 - 이은주; Lee, Eun-Joo (한국직업건강간호학회지, 2025)
Purpose: Burnout and job satisfaction are key factors influencing the turnover intention of general hospital nurses. This study aimed to identify the mediating effect of burnout and moderating effect of job satisfaction on the relationship between job stress and turnover intention among general hospital nurses. Methods: Participants were 201 nurses working at general hospitals in Changwon city, Republic of Korea. Data on turnover intention, job stress, burnout, and job satisfaction were collected between November 20 and to December 5, 2024. SPSS/WIN 23.0 and Process Macro 3.5 were employed to analyze the mediating and moderating effects. Results: Mean scores were as follows: Turnover intention (3.31±0.65), job stress (3.52±0.67), burnout (2.80±0.58), and job satisfaction (3.10±0.57). Job stress had a positive impact on turnover intention among hospital nurses (B=.42, p<.001), and the relationship between job stress and turnover intention was mediated by burnout (B=.14, 95% CI [0.07, 0.22]). Additionally, the positive influence of job stress on turnover intention was negatively moderated by job satisfaction. Conclusion: The significance of this study lies in its verification of the mechanism by which job stress influences turnover intentions among hospital nurses. Additionally, this study suggests that it is necessary to pay attention to job stress, burnout, and job satisfaction among hospital nurses to reduce turnover intentions.